Assessing the Quality of Care at Primary Health Care Level in Two Pilot Regions of Albania - Saric, Jasmina; Kiefer, Sabine; Peshkatari, Altina; Wyss, Kaspar (Frontiers in Public Health, 2021)
The quality of care (QoC) of primary health care (PHC) services in Albania faces challenges on multiple levels including governance, access, infrastructure and health care workers. In addition, there is a lack of trust in the latter. The Health for All Project (HAP) funded by the Swiss Agency for Development and Cooperation therefore aimed at enhancing the population’s health by improving PHC services and implementing health promotion activities following a multi-strategic health system strengthening approach. The objective of this article is to compare QoC before and after the four years of project implementation. A cross-sectional study was implemented at 38 PHC facilities in urban and rural locations in the Diber and Fier regions of Albania in 2015 and in 2018. A survey measured the infrastructure of the different facilities, provider–patient interactions through clinical observation and patient satisfaction. During clinical observations, special attention was given to diabetes and hypertensive patients. Infrastructure scores improved from base- to endline with significant changes seen on national level and for rural facilities (p < 0.01). Facility infrastructure and overall cleanliness, hygiene and basic/essential medical equipment and supplies improved at endline, while for public accountability/transparency and guidelines and materials no significant change was observed. The overall clinical observation score increased at endline overall, in both areas and in rural and urban setting. However, infection prevention and control procedures and diabetes treatment still experienced relatively low levels of performance at endline. Patient satisfaction on PHC services is generally high and higher yet at endline. The changes observed in the 38 PHC facilities in two regions in Albania between 2015 and 2018 were overall positive with improvements seen at all three levels assessed, e.g., infrastructure, service provision and patient satisfaction. However, to gain overall improvements in the QoC and move towards a more efficient and sustainable health system requires continuous investments in infrastructure alongside interventions at the provider and user level.